Increased prefrontal GABA concentrations in adults with autism spectrum disorders. Issue 7 (19th May 2022) - Maier, Simon; Düppers, Ansgard Lena; Runge, Kimon; Dacko, Michael; Lange, Thomas; Fangmeier, Thomas; Riedel, Andreas; Ebert, Dieter; Endres, Dominique; Domschke, Katharina; Perlov, Evgeniy; Nickel, Kathrin; et al.
Abstract: The excitatory‐inhibitory imbalance hypothesis postulates dysregulation of the gamma‐aminobutyric acid (GABA) and glutamate (Glu) neurotransmitter systems as a common underlying deficit in individuals with autism spectrum disorders (ASD). Previous studies suggest an important role of these systems in the pathophysiology of ASD, including a study of our group reporting decreased glutamate concentrations in the pregenual anterior cingulate cortex (ACC) of adults with ASD. The aim of this study was to replicate our previous findings of impaired glutamate metabolism in ASD in a new sample and to additionally quantify GABA in the ACC and dorsolateral prefrontal cortex (dlPFC). Concentrations of GABA and glutamate‐glutamine (Glx; combined glutamate and glutamine signal) were quantified in the ACC and dlPFC of 43 adults with ASD and 43 neurotypical controls (NTC) by magnetic resonance spectroscopy (MRS). The ASD group showed increased absolute GABA concentrations and elevated GABA/creatine ratios in the left dlPFC compared to NTC, while no group differences were detected in the pregenual and dorsal ACC. Previous findings of altered Glx concentration in the pregenual ACC of the ASD group could not be replicated. Regarding Glx concentrations and Glx/creatine ratios, there were no significant differences in the dlPFC and ACC either. The study supports the hypothesis of an altered GABA and glutamate equilibrium, indicating an imbalance between excitatory and inhibitory metabolism in ASD patients. However, inconsistent results across studies and brain regions suggest a complex underlying phenomenon. Lay Summary: Adults of the autism spectrum exhibit elevated levels of the inhibitory neurotransmitter GABA in the left dorsolateral prefrontal cortex. This finding supports the hypothesis of an imbalance between excitatory and inhibitory equilibrium in patients with autism spectrum disorders.